Análisis de capacidades burocráticas en organismos ambientales - Isuani, Fernando Javier (Universidad Nacional del Litoral, 2020)
The distance between the normative wish and the observable results in relation with environmental question suggest that the analyses on the subject of the bureaucratic capabilities of the state is an urgent matter of concern. This work suggest that need of an analysis at the national level in Argentina in order to produce public policies for the environmental sector. The work gives some conceptual and empirical elements to allow the acknowledgment of the bureaucratic capabilities of the state within the environmental field. It also describes the evolution of the subject at the national level and suggest a few propositions in order to led its discussion and future improvements.